Concentration protocol of rhenium-188 perrhenate eluted from tungsten-188/rhenium-188 generator for the preparation of high-yield rhenium-188-labelled radiopharmaceuticals. Issue 10 (October 2018) - Chhabra, Anupriya; Rathore, Yogesh; Bhusari, Priya; Vatsa, Rakhee; Mittal, Bhagwant R.; Shukla, Jaya
Abstract : Rhenium-188 ( 188 Re) is a β, γ emitter and considered a theranostic radionuclide. It is used for bone pain palliation, treatment of unresectable hepatocellular carcinoma, skin keloids, etc. 188 Re perrhenate is eluted from a 188 W/ 188 Re generator in large volumes (8–14 ml) of 0.9% normal saline. Concentrating 188 Re to 1–2 ml volume is important for high radiolabelling yield of various 188 Re radiopharmaceuticals, especially when the generator is old. For this, ion exchange column was prepared in-house, and 188 Re was concentrated using silver ion exchange column and QMA cartridge. 188 Re perrhenate eluted in saline was concentrated to 1 ml with more than 99% yield.